2018
DOI: 10.1103/physrevb.98.220411
|View full text |Cite
|
Sign up to set email alerts
|

Cavity optomechanics of topological spin textures in magnetic insulators

Abstract: Collective dynamics of topological magnetic textures can be thought of as a massive particle moving in a magnetic pinning potential. We demonstrate that inside a cavity resonator this effective mechanical system can feel the electromagnetic radiation pressure from cavity photons through the magneto-optical inverse Faraday and Cotton-Mouton effects. We estimate values for the effective parameters of the optomechanical coupling for two spin textures -a Bloch domain wall and a chiral magnetic soliton lattice. The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 55 publications
0
15
1
Order By: Relevance
“…This interference is tunable by both the strength and the direction of an external magnetic field, and can modify magnetically induced transparency (MIT) into a level attraction (LA)-like hybridization in the transmission. Different from previously reported systems with dissipative coupling [35][36][37][38][39][40][41][42][43][44][45][46] , negative mass 47 , or negative energy [48][49][50][51][52][53] , LA-like hybridization in our device is a special transmission response produced by destructive interference. This hybridization eliminates transmission and allows perfect absorption (96% in the experiment and 100% in the theory reported in this work).…”
contrasting
confidence: 77%
“…This interference is tunable by both the strength and the direction of an external magnetic field, and can modify magnetically induced transparency (MIT) into a level attraction (LA)-like hybridization in the transmission. Different from previously reported systems with dissipative coupling [35][36][37][38][39][40][41][42][43][44][45][46] , negative mass 47 , or negative energy [48][49][50][51][52][53] , LA-like hybridization in our device is a special transmission response produced by destructive interference. This hybridization eliminates transmission and allows perfect absorption (96% in the experiment and 100% in the theory reported in this work).…”
contrasting
confidence: 77%
“…Alternatively, Grigoryan and Xia have proposed an approach to explore level attraction [28] in hybrid magnon-photon systems, by modulating the relative phase [29] between coherent microwaves, and very recently Boventer et al [30] reported level attraction in these systems. Due to its potential applications in topological energy transfer, quantum sensing, and nonreciprocal photon transmission, level attraction has been of great interest in studies of other systems, such as in Bose-Einstein condensated quantum systems [31,32], microcavity polariton systems [33] and cavity optomechanical systems [34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…For example, either the oscillator or the dissipative third-party can be superconducting qubit [6,23], dielectric nanostructures [24], antiferromagnets [25,26], high-order spin wave modes [27] or other excitations such as phonons [28]. It has been reported recently that magnetic textures can also be coupled with the cavity photons [29,30]. Based on the understanding of dissipative coupling, the nonlinear effect [31,32] and topological properties of exceptional point [33][34][35][36] can be generalized and new physics is expected.…”
mentioning
confidence: 99%